Therapeutic skills in speech therapy: practitioner and patient perspectives - Calabuig-Sanfeliu, Beatriz; Cervera-Mérida, José Francisco; Ygual, Amparo (Revista de Investigación en Logopedia, 2024)
Health professions are moving towards a patient-centred clinical model, heir to the biopsychosocial model, characterised by its holistic understanding, the helping relationship and shared decision making. This model requires professionals to have therapeutic skills that favour the relationship and the subjective well-being of the patient. This study explores the views of speech and language therapists and patients on the role of these skills, which they consider most important, and how work experience influences their perceptions. A total of 558 participants were divided into two groups: Professionals and patient relatives. Data were collected using separate forms for speech and language therapists and patients. Group responses were compared and correlated with work experience. Patients value therapeutic skills more than knowledge and experience. Professionals value knowledge more as they gain experience and make decisions based on evidence or their own judgement rather than on an exchange of information with the patient. The therapeutic skill most valued by both groups is empathy, and this appreciation increases with experience. Patients associate the professional's excellence with their therapeutic skills. Patients place the highest value on therapeutic skills and speech and language therapists give them a very important role, equating them with knowledge. These results support the idea that speech and language therapists have adopted the biopsychosocial model, but do not confirm that they apply Shared Decision Making, the core of the patient-centred clinical model.
Keywords: Therapeutic Skills; Speech-Language Therapy; Patient-Professional relationship; Empathy